Estetika Karya Lukis Afianto Arifin - Selvina Rahmi; Suryanti Suryanti; Miswar Miswar (Institut Seni Indonesia Padang Panjang, 2021)
This study discusses Afianto Arifin's tendency to persist with a strong naturalism style during the incessant contemporary art. This study also discusses the journey of art, the factors behind his work attitude, and the aesthetic concepts contained in his paintings. To answer these problems, qualitative research methods are used which include observation, interviews, and literature study. The research was conducted in the City of Bukittinggi and Padang Pariaman district, West Sumatra province. Based on the research results, the beginning of Afianto Arifin's artistic career began in Jakarta. Apart from painting, Arifin also got a project to make sculptures and reliefs. After that, Arifin was diligent in making paintings. Arifin tends to raise objects of natural scenery and women's beauty. The idea of creating Arifin's paintings was influenced by artistic factors and cultural factors in his native area, namely Bukittinggi. The aesthetic concepts contained in Arifin's paintings are discussed from the point of view of art styles, art structures, as well as the interaction of media and meaning. Arifin is a person who tends to not want to be exposed and does not like to see exhibitions, this makes Arifin stick to his ideals and influences his artistic style until now.